PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM SEKTOR JASA DI KOTA BATAM - Eginta imanuel sembiring; Cindy Cindy; Azizul Syukriansyah; Malvin Agustino; Jacky Gunadi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Research conducted by Metropolis Batam Pos in 2022 recorded as many as 120,567 units of cars used by the people of Batam city and this number continues to increase in the following years. Based on these data, it can be concluded that the opening of car wash services in Batam can be sustainable, so the kongkow carwash was opened. The method of collecting information is through interviews & observations. The results of interviews & observations conducted, it can be said that the marketing & development method carried out by Kongkow Carwash is by distributing brochures to introduce their business and providing information about Kongkow Carwash services to the people of Batam City, in addition to distributing vouchers or coupons.